Superior cuproptotic efficacy of diethyldithiocarbamate-Cu4O3 nanoparticles over diethyldithiocarbamate-Cu2O nanoparticles in metastatic hepatocellular carcinoma - Abu-Serie, Marwa M.; Barakat, Assem; Ramadan, Sherif; Habashy, Noha Hassan (Frontiers in Pharmacology, 2024)
Metastatic hepatocellular carcinoma (HC) is a serious health concern. The stemness of cancer stem cells (CSCs) is a key driver for HC tumorigenesis, apoptotic resistance, and metastasis, and functional mitochondria are critical for its maintenance. Cuproptosis is Cu-dependent nonapoptotic pathway (mitochondrial dysfunction) via inactivating mitochondrial enzymes (pyruvate dehydrogenase "PDH" and succinate dehydrogenase "SDH"). To effectively treat metastatic HC, it is necessary to induce selective cuproptosis (for halting cancer stemness genes) with selective oxidative imbalance (for increasing cell susceptibility to cuproptosis and inducing non-CSCs death). Herein, two types of Cu oxide nanoparticles (Cu4O3 "C(I+II)" NPs and Cu2O "C(I)" NPs) were used in combination with diethyldithiocarbamate (DD, an aldehyde dehydrogenase "ALDH" inhibitor) for comparative anti-HC investigation. DC(I+II) NPs exhibited higher cytotoxicity, mitochondrial membrane potential, and anti-migration impact than DC(I) NPs in the treated human HC cells (HepG2 and/or Huh7). Moreover, DC(I+II) NPs were more effective than DC(I) NPs in the treatment of HC mouse groups. This was mediated via higher selective accumulation of DC(I+II) NPs in only tumor tissues and oxidant activity, causing stronger selective inhibition of mitochondrial enzymes (PDH, SDH, and ALDH2) than DC(I)NPs. This effect resulted in more suppression of tumor and metastasis markers as well as stemness gene expressions in DC(I+II) NPs-treated HC mice. In addition, both nanocomplexes normalized liver function and hematological parameters. The computational analysis found that DC(I+II) showed higher binding affinity to most of the tested enzymes. Accordingly, DC(I+II) NPs represent a highly effective therapeutic formulation compared to DC(I) NPs for metastatic HC.